Nota sobre a biologia de "Microdon tigrinus" (Diptera: Syrphidae), parasito social de "Acromyrmex coronatus" (Hymenoptera: Formicidae) - Camargo, R.S.; Forti, L.C.; Fujihara, R.T.; Carlos, A.A.; Matos, C.A.O. (My University, 2008)
The fly of the syrphid Microdon tigrinus is a specific social parasite of leaf-cutting ant, Acromyrmex coronatus. Six colonies of Acromyrmex coronatus were collected in plastic containers, which there was a layer of 1 cm of plaster, with the purpose of maintaining the humidity of fungus culture. Larvae of social parasite were separate for the establishment of instars number, through morphometric study. The data were measured of 165 larvae, using spiracle (length (Ls), width (Ws) and distance between spiracle (Ds)). After that, the morphometric data obtained for the larvae were submitted to cluster analysis by Wong's hybrid method, which produces the adequate number of groups through pseudo F-statistics and pseudo t-squared statistics. The three morphometric variables studied permitted grouping of larvae into the following three distinct groups: cluster 1 [long dash] consisting of 55 larvae (Ls=0.177[plus or minus]0.026, Ws=0.163[plus or minus]0.030, Ds=0.052[plus or minus]0.008 mm); cluster 2 - consisting of 20 larvae (Ls=0.631[plus or minus]0.065, Ws=0.630[plus or minus]0.049, Ds=0.065[plus or minus]0.018 mm); cluster 3 - consisting of 90 larvae (Ls=1.294[plus or minus]0.062, Ws=1.308[plus or minus]0.069, Ds=0.140[plus or minus]0.018 mm). of the all couples, only 1 obtained success in the mating, and the female, after 24 hours, began the oviposition. The female layed 76 eggs in a period of 6 days, after that, her death. The larvae emerged in the seventh day (incubation period [plus or minus] 7 days). From 76 eggs, 54 were viable, with a viability of 71.05%. This study contributes to the knowledge of Microdon tigrinus biology of, a social parasite poorly studied in Brazil.
Notes about biology of Microdon tigrinus (Diptera: Syrphidae), social parasite of Acromyrmex coronatus (Hymenoptera: Formicidae).